Money, money, money - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
In November 2000, the Ford Foundation launched the International Fellowships Program (IFP), providing US$280 million over the next 10 years for post-baccalaureate students in selected countries, including some in Africa. The IFP will award 350...